Canola Cost-Return Budget in South Central Kansas - Dhuyvetter, Kevin C.; Duncan, Stewart R. (My University, 2001)
This publication contains information for a projected budged reflecting expected income and cost based on canola production practices in south central Kansas.
MF2421_2001_10
Keywords: MF2421; Crops; Economics; MF